Find: g(f(h(-3)))

f(x) = 2x

g(x) = -3x+4

h(x) = 2x-8

### 1 Answer | Add Yours

Given f(x)=2x,g(x)=-3x+4, and h(x)=2x-8 find g(f(h(-3))):

(1) One way is to evaluate from the inside out:

h(-3)=2(-3)-8=-14

f(-14)=2(-14)=-28

g(-28)=-3(-28)+4=88

**So g(f(h(-3)))=88**

(2) Another way is to find the expression for g(f(h(x))) and substitute -3 for x:

h(x)=2x-8

f(h(x))=2(2x-8)=4x-16

g(f(h(x)))=-3(4x-16)+4=-12x+52

So g(f(h(-3)))=-12(-3)+52=36+52=88 as before.

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes